PENINGKATAN PENGUASAAN KOSAKATA BAHASA ARAB MELALUI METODE CONTOH MORFOLOGI: (Penelitian Tindakan di Fakultas Agama Islam) - FITRILIZA FITRILIZA; Ari Khairurrijal Fahmi (Jurnal Pendidikan Islam, 2017)
This research aims to get a deep understanding about using of learning methods with examples, exercises and independent work to improve the mastery of Arabic vocabulary in the faculty of Islamic religion, Muhammadiyah University Prof. Dr. Hamka. The method of this reasearch is a mix method that combines both qualitative and quantitative methods. Qualitative method with cycle content analysis technique while quantitative use descriptive statistic. Stages of research begins with a pre test of students who become samples, then performed an action (treatment) in the form of cycles, then performed post test, then the process of conclusion. The population in this study is all students of Islamic religious faculty who are following an Arabic language courses. The sample is a student of second semester and sixth semester. Data is processed by frequency distribution table technique. The results showed that the ability of Arabic vocabulary mastery of faculty of Islamic studies UHAMKA students Increased after students learn Arabic with the method of morphological example. Key Words : Arabic Vocabulary, Example, morphology,